Are Resources and Support Necessary or Just Nice in Post-program Application? - Judith M. Ottoson (Adult Education Research Conference, 1998)
This study uses matched survey data (n=1356) to explore the relationship between post-educational application and five contextual variables. Significant positive associations were found between contextual and outcome variables; significant differences were found between post and follow-up ratings of contextual variables. What happens after adult education programs may have more effect on post-educational application than what happens during educational programs.